Hydrological and Morphological Characterization of the Sô River Basin in South-East of Benin (West Africa) - KOUDENOUKPO, Cosme; CHIKOU, ANTOINE (My University, 2017)
As a prelude to a large ecological quality assessment study, the Sô River, a watercourse in southern Benin, has been characterized on the hydrological and morphological levels. The study was conducted for a year from June 2015 to May 2016 with a monthly frequency of data collection. At the end of this large sampling campaign, the determination of the long and cross-sectional profiles of the Sô River made it possible to clearly distinguish a upper course, an average course and a lower course, all characterized by morphological and riverine diversity. These sectors have particular biophysical characteristics. The representation of the bathymetric map of the river shows an average depth of 3m and a maximum of 6.5m. Finally, river flow facies have some general structural and functional uniformity in terms of current velocity, bathymetry, substrate particle size, bed slope and cross-sectional profiles. All this militates in favor of a dynamic equilibrium of the Sô River reflecting a good hydro-morphological state except for its slightly disturbed lower course.
Keywords: Hydrology; Morphology; Bathymetry; Basin; Sô River; Benin